(untitled) (Práxis Educativa, 2024)
Schools around the world underwent rapid changes when they faced the emergency situation caused by the COVID-19 pandemic. The aim of this paper is to analyse the variables identified in the scientific literature of studies that aimed to understand the impact of educational inequalities during the COVID-19 emergency distance education. A systematic review was conducted, which included the analysis of variables related to the sample and the methodology used. The PRISMA method was applied in three phases. The sample consisted of 298 articles that met the inclusion criteria. The results are divided by year, country, sample characteristics, educational levels, intervention strategies and methodological approaches. This research shows that educational inequalities are not fully addressed in the studies, as there is inequality based on belonging to the educational community or nationality. Keywords: Inequality. Emergency education. Distance education. Coronavirus. Systematic review.